Effect of special horticultural practices on physical and chemical parameters in fruit of mango (Mangifera indica L.) cv. Ratna - Aghav, R.D.; Haldankar, P.M.; Malshe, K.V.; Parulekar, Y.R.; Saste, H. A.; Samant, A. P. (International Journal of Environment, Agriculture and Biotechnology, 2024)
The investigation was conducted on mango at College of Horticulture, Dapoli, Dist. Ratnagiri (MS) during the year 2020-21 to assess the effect of special horticultural practices on physical and chemical parameters in fruit of mango (Mangifera indica L.) cv. Ratna. The experiment was laid out in RBD with three replications and ten treatments viz; girdling on first fortnight of October (T1), girdling on first fortnight of November (T2), girdling on first fortnight of October and November (T3), girdling on first fortnight of October and tip pruning (T4), girdling on first fortnight of November and tip pruning (T5), girdling on first fortnight of October and November and tip pruning (T6), tip pruning (T7), removal of new shoots below old shoot (T8), smudging (T9) and control (T10). Treatment girdling on first fortnight of October and November and tip pruning resulted highest fruit weight, fruit length, fruit diameter, pulp weight, pulp stone ratio at harvest stage and ripe stage. The chemical parameter TSS, reducing sugar, total sugar, acidity, pH and ascorbic acid were non-significant at both stages.